TRADISI ADAT PERKAWINAN SUKU SAKAI DI KECAMATAN BONAI DARUSSALAM KABUPATEN ROKAN HULU - Yuresha Febrianti Fahmi; Ridwan Melay; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: Indonesian society has a diverse life of races, ethnicities, languages and culture. Diversity is based on environmental conditions that havean impact on aspects of social life and are character by some people who are still living traditionally and modern. One of them is the life style of the Sakai who still perform traditional ceremonies in the traditional form such as traditional wedding ceremonies. The purpose on the study was 1) to find out the history of the Sakai 2) to find out the traditional marriage of the sakai in the Bonai Darussalam 3) to find out the purpose of the sakai marriage customs of the Sakai in Bonai Darussalam 4) to know the Religion of the Sakai 5) to find out to preserve The traditional marriage traditions of the Sakai community in the Bonai Darussalam. As for this study using Qualitative methods with data collection teahniques through interview, observation, literature study and documentation. The result of this research is that the sakai marriage system has a procedure that starts with the stage before marriage, the marriage ceremony stage therew is a series, which in each stage there is a series of the activities that are very thick with there customs, in the customs of marriage it also hasa several objectivies including to preserve the Sakai trible culture that has existed since its ancestions.Key Words: The Traditional Marriage Tradition of the Sakai Bonai Darussalam Rokan Hulu.